Menyesuaikan Tata Kelola Lingkungan Dengan Tantangan Sosial dan Ekologis Dalam Konservasi Keanekaragaman Hayati - Fernanda, Hengki; DESSY ANGRAINI; PEBI JULIANTO3; HADI CANDRA; WAZIRMAN (Jurnal Khazanah Intelektual, 2026)
The dynamics of public policy in Indonesia are often ineffective in exploring existing problems. This research aims to identify and analyze public policies through a literature study approach. This research reveals the gap between policy formulation and implementation and offers a new perspective on how to optimize and implement development policies. By analyzing various academic sources, this research shows that the lack of coordination between government agencies and the lack of public participation are the main obstacles to achieving policy objectives. This research uses a systematic literature review method that focuses on three main aspects effectiveness, policy implementation public participation in the policy process, and the impact of policies on society. In addition, this research reveals that policies designed by considering the local context and actively involving stakeholders tend to be more successful in achieving the desired goals